The Dynamics of Social Interaction in the Context of Islamic Law and Politics - Azizah, Azzah; Andaryuni, Lilik (International Journal on Advanced Science, Education, and Religion, 2025)
This study explores the dynamics of public interaction with issues of Islamic law and politics within the social, cultural, and political context of Indonesia. These interaction patterns are deeply rooted in the historical trajectory of Islamic politics and the role of religion as a value system that shapes public behavior and political decision-making. The relationship between Islamic law and politics reflects a dynamic interplay influenced by various factors, including historical and cultural backgrounds, economic conditions, religious interpretations, education, media, and global as well as social transformations. In practice, Islamic law functions both as a source of moral and ethical guidance and, at times, as a political tool that can generate tension within Indonesia’s multicultural society. Islam’s core principles—such as justice, deliberation (musyawarah), human rights protection, and fair leadership—encourage active civic engagement in legal and political affairs. Moreover, religion plays a pivotal role in shaping group identities and social relations, especially in the context of ongoing social change. The perspectives of scholars such as Al-Ghazali and Muhammad Abduh illustrate varied approaches to the relationship between religion and the state, ranging from integrative to secularist views. This study highlights the critical need for dialogue, inclusivity, and contextual approaches in understanding and implementing Islamic law and politics in Indonesia, in order to foster a just and civilized sociopolitical order that aligns Islamic values with modernity and societal diversity.